COVID-19 PANDEMIC TERMS FORMATION IN ARABIC VOCABULARY ON THE DICTIONARY OF COVID-19 TERMS: LEXICOLOGICAL STUDIES - Muhamad Saiful Mukminin; Khoirunnisa Rahmawati; Nilna Dati Layyina (Afshaha: Jurnal Bahasa dan Sastra Arab, 2024)
In linguistic studies, especially lexicology, the existence of the Covid-19 Pandemic has contributed to the formation of linguistic terms. This study aims to describe the formation process of Covid-19 pandemic terms in English and Arabic. Data were collected from primary data sources, i.e. Dictionary of Covid-19 Terms. This research is a qualitative research with descriptive method. This research is a qualitative research with descriptive method. Data collection was carried out using the reading and note-taking technique. The data analysis used adopted an interactive data analysis model that consists of data reduction, data presentation, and conclusion/verification. The results of this study are 188 data of Covid-19 Pandemic terms in English and Arabic formed through two variants. The single variant consists of foreign term translation as much as 111 (61%) data, Arabic vocabulary as much as 62 (34.1%) data, adoption as much as 4 (2.2%) data, composition as much as 3 (1.6%) data, adaptation as much as 1 (0.5%) data, and acronymization as much as 1 (0.5%) data. The couplet variants consist of a combination of foreign term translation and adaptation combination as much as 3 (50%) data, translation of foreign terms and abbreviation as much as 1 (16.7%) data, composition and abbreviation as much as 1 (16.7%) data, and composition and adaptation as much as 1 (16.7%) data.